Penerapan Metode Bermain Dalam Meningkatkan Kreativitas Siswa di Sekolah Dasar - Nurhairunisah, Nurhairunisah; Indah, Indah; Adiansha, Adi Apriadi (JGSD: Jurnal Guru Sekolah Dasar, 2025)
The Application of the Play Method in Enhancing Creativity among Elementary School Students is a study motivated by the need to improve students' creative thinking skills through innovative educational approaches. This research aims to evaluate the effectiveness of the play method as a teaching strategy in developing student creativity, using quantitative data obtained from pre-tests and post-tests. The research employs a quasi-experimental design involving two classes: an experimental class that applies the play method and a control class that uses conventional teaching techniques. Creativity measurement instruments include criteria-based creativity tests and direct observations, supplemented by statistical analysis to measure significant changes. The main results indicate a significant improvement in student creativity in the experimental class compared to the control class, alongside higher achievement of learning objectives. These findings demonstrate that the play method not only enhances creativity but also deepens comprehensive understanding of concepts. What sets this study apart is its integration of interactive digital technology into the play process, distinguishing it from previous research. This innovative approach enables the development of game scenarios tailored to the individual needs of students, thereby increasing engagement and providing more personalized and effective learning outcomes. Consequently, the study offers a new perspective on applying the play method to optimize creativity in the elementary education environment